Aqueous photochemical degradation of BDE-153 in solutions with natural dissolved organic matter. (July 2016) - Wang, Huili; Wang, Mei; Wang, Hui; Gao, Jiajia; Dahlgren, Randy A.; Yu, Qing; Wang, Xuedong
Abstract: The compound 2, 2′, 4, 4′, 5, 5′-hexabrominated diphenyl ether (BDE-153) is an intermediate photolytic product in the degradation of highly brominated diphenyl ethers to lower brominated forms. Herein, we report the effects of two natural organic matter (NOM) sources, Suwannee River fulvic acid (SRFA) and Pony Lake fulvic acid (PLFA), on BDE-153 photolysis in water. The rate constant ( k ) and half-life of BDE-153 was 2.26 × 10 −2 min −1 and 30.72 min under UV–Vis irradiation (direct photolysis at λ > 290 nm). The k value for BDE-153 decreased markedly in the presence of NOM with a larger decrease in the presence of PLFA than SRFA. Electron spin resonance (ESR) demonstrated generation of free radicals in the photolytic process that mainly involved 1 O2 and OH. The biomolecular k values for reaction of 1 O2 and OH with BDE-153 were 3.65 × 10 6 and 7.70 × 10 8 M −1 s −1, respectively. The contribution of OH (28.7–31.0%) to the indirect photolysis of BDE-153 was higher than for 1 O2 (12.9–14.9%). The photolytic rate of BDE-153 in oxygen-rich (aerated) solution was much slower than in oxygen-poor (nitrogen-sparged) conditions, demonstrating that 3 NOM* is a more effective reagent for degradation of BDE-153 than 1 O2 . Addition of sorbic acid (a 3 NOM* quencher) significantly reduced the photolytic rate of BDE-153 confirming the important role of 3 NOM* in indirect photolysis. In the presence of NOM, BDE-153 indirect photolysis was facilitated mainly by reaction with 3 NOM* and OH. To the best of our knowledge, this is the first comprehensive investigation of indirect photolysis of BDE-153 in water containing NOM. Graphical abstract: Generation of OH and 1 O2 in process of BDE-153 photolysis in water by ESR technique. Sorbic acid (a 3 NOM* quencher) and oxygenated or deoxygenated experiments showed that excited state NOM* played a key role in the photochemical transformation of BDE-153. Highlights: Generation of OH and 1 O2 in process of BDE-153 photolysis in water by ESR technique. The contribution of OH (28.7–31.0%) to the indirect photolysis of BDE-153 was higher than that of the 1 O2 (12.9–14.9%). The indirect photolysis of BDE-153 containing NOM is primarily attributable to OH and 3 NOM*.